Determination of Thermal Diffusive Properties of Silver and Copper - Shah, Zulfiqar Ali; Arshad, Nimra; Sabir, Sidra (Recent Trends in Chemical and Material Sciences Vol. 2, 2021)
Being the most abundant and least expensive of the noble and precious metals, such as copper (Cu) island on silver (Ag) with excellent electrical and thermal conductivity, copper is used extensively in electrical power transmission, plumbing, cookware, etc. The important properties of silver include its good electrical conductivity and its chemical stability. Bulk Ag is a common material for high-quality reflectors of electromagnetic radiation in the visible regime, superseding cheaper non-noble metals such as aluminum. At three different temperatures 300, 500 and 700 K the diffusion is carried out. The lattice parameter has been calculated for Ag and compared with the experimental values. It is found that by increasing in temperature the rate of diffusion also increases. The diffusion prefactor is 5.24 × 1011 Å2/s. So far the experimental and theoretical work for other islands shows that the effective energy barrier and diffusion coefficient have Arrhenius plot gives the effective energy barrier value of 143.56 meV and diffusion prefactor value of 5.24 × 1011 Å2/s for 10-atom island. The values of diffusion coefficient and effective energy barrier are in the same range as for the other islands regarding the theoretical and experimental work done so far. At 300 K, the fissures and dislocations have been observed near the island. However, these conclusions are in agreement with the recent findings using ab-initio electron structure calculation.